Discussion on the Education Path of Socialist Core Values for College Students - Chen, Jinxu (Transactions on Social Science, Education and Humanities Research, 2024)
College student party members are in the critical period of maturing their world view, outlook on life and values, and their value orientation and ideological concepts are easily strongly influenced by various external factors and social environment, which brings about many violent shocks at the value level, which has a negative impact on the formation and development of college students' values to a certain extent. After the Party Central Committee put forward the core socialist values, college student party members are required to accurately understand and grasp the connotation of the core socialist values, and understand their value goals, value orientations and value standards at the national, social and individual levels. Only by comprehensively investigating and researching the cognitive, emotional and practical identity of college student party members in the field of socialist core values, analyzing the problems existing in the field of socialist core values education, and proposing a systematic and effective educational path for socialist core values on this basis, can college student party members firmly establish the socialist core values, form a correct "three views", and have good cognitive, emotional and practical identity.